Improvement of Organizational Measures for Detection and Diagnosing of Tuberculous Infection and Tuberculosis in Adolescents in the Republic of Kazakhstan - L. T. Eralieva; K. S. Serikbaeva; A. S. Rakisheva; Z. S. Bekbenbetova; O. G. Prikhodchenko (Туберкулез и болезни лёгких)
The objective: to improve organizational measures for detection and diagnosing of tuberculous infection and tuberculosis in adolescents in the Republic of Kazakhstan.Subjects and Methods. Screening was conducted among 27,648 adolescents aged 15-17 years from regions of the Republic of Kazakhstan with a high burden of tuberculosis. It was planned to use TRA tests and fluorography in parallel, while local doctors, district and school nurses, and nurses in vaccination rooms were preliminary trained by pediatric phthisiologists to perform the test, evaluate its results and monitor manifestations of adverse events (AEs) caused by TRA test.Results. 27,648 adolescents (aged 15-17 years) were given TRA test. No adverse events were observed during TRA skin test. Latent tuberculous infection was diagnosed in 320 (1.2%) adolescents. During further examination, 10 patients were diagnosed with drug susceptible pulmonary tuberculosis with no bacillary excretion. Based on the study results, to detect LTBI and tuberculosis in adolescents, in addition to fluorography examination, it is necessary to use TRA skin test with in the groups facing a high risk of tuberculosis.